COMPARISON OF PROPERTIES OF CELLULOSE NANOMATERIALS OBTAINED FROM SUNFLOWER STALKS - DURMAZ, EKREM; ATES, SAIM (Institutul de Chimie Macromoleculara Petru Poni, 2021)
This study aimed to investigate the usability of sunflower stalks, which is one of the most significant agricultural residues in Turkey, in the production of cellulose nanomaterials (CNMs). Cellulose nanofibrils (CNFs) and cellulose nanocrystals (CNCs) were produced by using a grinding method and acid hydrolysis, respectively. The average width and length of CNCs were found as 13.91 ± 3.09 nm and 60.44 ± 21.06 nm, respectively. Besides, the average width of CNFs was determined as 15.03 ± 3.68 nm. The crystallinity index of CNFs and CNCs was determined as 82.64% and 83.09%, respectively. Although the main thermal degradation stage of CNCs started at higher temperature than that of CNFs, the latter were more stable than CNCs at high temperatures. Furthermore, the chemical bonds in the raw material, bleached fiber, CNCs and CNFs were investigated with FTIR analysis. Consequently, it was seen that sunflower stalks can be a suitable raw material for the production of CNMs.
Keywords: 2. Zero hunger